Evaluation of self-directed learning readiness among undergraduates in a medical college in Tumakuru - K. S., Ramya (International Journal Of Community Medicine And Public Health, 2025)
Background: Self-directed learning (SDL) enables medical students to take charge of their own learning objectives, process, methods and self-evaluation thereby prepares them as lifelong learners. SDL readiness (SDLR) is the measure of capabilities and attitudes of students individually towards involvement in SDL. This helps teachers to understand and take proper measures to improve students’ SDLR. Methods: A cross-sectional study was carried out among 120 medical undergraduate students in Sri Siddhartha medical college selected through multistage sampling. SDLR was assessed using validated Fisher’s scale administered through Google form after obtaining informed consent. Data was analysed using statistical package for social sciences (SPSS) v 21. Results: The mean age of students was 20.9±1.52 years, around 53% were males, 47% were females and 83% belonged to the Hindu religion. The mean SDLR score was 132±12.61. Taking the standard cut off score of 150, it was found that around 32% of the study participants showed high readiness and 68% showed low readiness. Statistically significant association was found between SDLR scores and percentage of marks scored in 12th class. Conclusions: SDLR among medical undergraduates in the present study is low. There was no significant association with other socio-demographic except for percentage in 12th class. Introduction of different strategies of SDL like use of online courses, digital libraries, e-books, pre-recorded lectures and game-based learning might be necessary to motivate students to improve their SDLR.